Integrated marketing strategy to improve financial efficiency in hospitals - Febrianti, Reni; Sutrisno, Sutrisno; Parso, Parso (Edelweiss Applied Science and Technology, 2025)
Hospital sustainability is critical to the SDGs, requiring cost and technology efficiency, but it faces challenges of high upfront costs. Operational changes, complex regulations, and supplier dependency hamper cost efficiency. Sustainability requires green and social strategies. Previous studies have shown that efficient cost management strategies are important, with specific challenges such as diversification, risk, and code errors. However, high investment, technology dependency, cybersecurity, automation, and insurance collaboration affect hospital flexibility and operations. The study offers insights into how hospitals invest in technology, staff training, and cybersecurity to improve integrated marketing strategies for the financial efficiency of hospitals in the Jakarta area of Indonesia. This study will analyze hospital marketing strategies to improve financial efficiency. It analyzes hospital financial efficiency using SWOT and QSPM. These two strategic analysis tools are used to identify strengths, weaknesses, opportunities, and threats that affect hospital financial efficiency. The results of this study will be used to provide strong, data-driven strategic recommendations. Hospitals must adapt to changes in healthcare technology through investment in technological innovation and staff training. Implementing modern technology and automating registration systems will improve operational efficiency and patient satisfaction. In addition, it highlights the hospital’s strategic priorities to increase competitiveness: investment in technology and staff training, transparent pricing policies, cybersecurity and electronic medical records, automation for operational efficiency, and collaboration with insurance and digital marketing. These strategies are essential for the relevance and efficiency of hospital services.